Transmit antenna selection systems : A performance comparison of different types of receiver schemes - Tan, Beng Soon (2013)
In this survey article, we compare the performance of single transmit antenna selection (TAS) systems with different kinds of receiver schemes. These systems include the TAS/switch-and-examine combining (TAS/SEC), TAS/SEC with postselection (TAS/SECPS), TAS/generalized selection combining (TAS/GSC), and TAS/output-threshold generalized selection combining (TAS/OT-GSC) systems. The performance comparisons are made in terms of the average output signal-to-noise ratio (SNR), symbol-error rate (SER), the number of channel estimates Ne, and the number of branches required for processing Np . It is shown that the TAS/SECPS and TAS/OT-GSC systems can achieve similar performance compared with the TAS/selection combining (SC) and TAS/GSC systems, respectively, with a reduced number of both channel estimates and branches required for processing when the predetermined SNR threshold is optimized.